Kualitas Pelayanan dan Kepuasan Konsumen di Bandar Udara Internasional Soekarno-Hatta - Ida Nuraida; Vincentia Wahju Widajatun; Lilian Danil (Research Report - Humanities and Social Science, 2015)
The role of airports as a meeting place between the users of air transportation ( passenger ) and air transportation providers (airlines) is very important. Satisfaction of the passengers is an important part of the service at the airport. An independent, agency Skytrax, conducted a survey on customer satisfaction to the passengers from the international airport in the world, and the results of customer satisfaction index to Soekarno-Hatta international airport is still not satisfactory. Researchers try to find out whether the passenger’s perception of service quality related to satisfaction of Soekarno-Hatta airport. Benchmarking of service quality of Soekarno–Hatta, with Changi and Hongkong, were intended to facilitate analysis and give solution for PT Angkasa Pura. This research using qualitative and quantitative method. Data collected from observation, interviews and questionnaires. Data from questionnaires has been processed with confirmatory analysis and Structural Equation Modelling. Keyword: service quality, airport, customers satisfaction